Corporate Restructuring in Austria: The Implementation of Directive (EU) 2019/1023 on Restructuring and Insolvency - Wilfinger, Alexander (European Insolvency and Restructuring Journal, 2023)
Implementing the Directive (EU) 2019/1023 on Restructuring and Insolvency, the Austrian Restructuring Act came into force on 17 July 2021. This paper introduces the new restructuring scheme and provides an overview of its concepts, advantages and weaknesses.